2008
DOI: 10.2967/jnumed.108.052126
|View full text |Cite
|
Sign up to set email alerts
|

The Biodistribution and Radiation Dosimetry of the Arg-Gly-Asp Peptide 18F-AH111585 in Healthy Volunteers

Abstract: We report the safety, biodistribution, and internal radiation dosimetry of a new PET tracer, 18 F-AH111585, a peptide with a high affinity for the a v b 3 integrin receptor involved in angiogenesis. Methods: PET scans of 8 healthy volunteers were acquired at time points up to 4 h after a bolus injection of 18 F-AH111585. 18 F activity in whole blood and plasma and excreted urine were measured up to 4 h after injection. In vivo 18 F activities in up to 12 source regions were determined from quantitative analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
49
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 9 publications
3
49
0
1
Order By: Relevance
“…Preliminary clinical studies with 18 F-AH111585 have already proven that this radioligand has a suitable biodistribution and dosimetry profile (36) and can successfully image metastatic breast cancer lesions (7): 7 patients with a total of 18 tumors detectable on CT were imaged with 18 F-AH111585 PET, and all tumors were visible.…”
Section: Resultsmentioning
confidence: 99%
“…Preliminary clinical studies with 18 F-AH111585 have already proven that this radioligand has a suitable biodistribution and dosimetry profile (36) and can successfully image metastatic breast cancer lesions (7): 7 patients with a total of 18 tumors detectable on CT were imaged with 18 F-AH111585 PET, and all tumors were visible.…”
Section: Resultsmentioning
confidence: 99%
“…Integrin imaging originally based on the use of argininge-glycine-aspartic acid (RGD) based radioligands. McParland et al [80] tested first the [ F-galacto-arginine-glycine-aspartic-acid ( 18 F-galacto) RGD in sixteen patients with primary ( =12) or metastatic breast cancer ( =4) and they found that all the primary tumors and metastases were clearly identified [53,81].…”
Section: Integrinsmentioning
confidence: 99%
“…18 F-fluciclatide is a cyclic tripeptide that contains the RGD sequence and binds with high affinity to integrins a v b 3 and a v b 5 , both of which are upregulated in tumor-associated vasculature (18). 18 F-fluciclatide is currently being developed as a radiotracer for the imaging of angiogenesis in tumors and consequently as a biomarker of response to antiangiogenic therapies (14,19).…”
mentioning
confidence: 99%